2006
DOI: 10.1080/13880200600713667
|View full text |Cite
|
Sign up to set email alerts
|

Bark and Fruit Extracts ofGmelina arborea. Protect Liver Cells from Oxidative Stress

Abstract: The effect of Gmelina arborea Roxb. (Verbenaceae) bark and fruit aqueous extracts on paraquat-and hydrogen peroxide-induced oxidative stress was investigated using liver slice culture. Both paraquat and hydrogen peroxide were found to be cytotoxic as measured by release of lactate dehydrogenase from liver slice culture. Addition of bark and fruit extracts along with these cytotoxic agents led to a decrease in lactate dehydrogenase release. Activities of three antioxidant enzymes, namely superoxide dismutase, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…[10] Crude extracts of the plant are reported to possess wound-healing properties, [11] antidiarrheal activity, [12] antioxidant activity, [13] antiulcer activity, [14] and antidiabetic activity. [15] Toxicity studies of aqueous extract have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Crude extracts of the plant are reported to possess wound-healing properties, [11] antidiarrheal activity, [12] antioxidant activity, [13] antiulcer activity, [14] and antidiabetic activity. [15] Toxicity studies of aqueous extract have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Heartwood of Gmelina is used as an ingredient in many well-known Ayurvedic and herbal preparations like Dashmula and Chyawanprasha and is therefore much used in a variety of diseases. [6,10] Pharmacological studies indicating antiinflammatory [11,12], antioxidant [13], antimicrobial [14], anti-ulcer [15] and wound healing [16] potential of different plant parts are well reported. The plant extracts are also reported for their hypolipidemic activity [17], antidiabetic activity [18], anti-diarrhoeal activity [19] and immunomodulatory activity [20].…”
Section: Introductionmentioning
confidence: 99%
“…Different extracts of the plant are reported to have wound-healing properties (Shirwaikar et al, 2003), antidiarrheal activity (Agunua et al, 2005), and antioxidant activity (Sinha et al, 2006).…”
mentioning
confidence: 99%